STOCHASTIC CELLULAR MODEL FOR LOWLAND URBAN DEVELOPMENT - K. Teknomo; G. P. Gerilla; K. Hokao (Lowland Technology International, 2006)
An urban growth model using stochastic cellular simulation was developed with motivation to understand the consequence of zone management policies in lowland cities. The model could integrate the growth, decline, spread, intensification, and protected areas of the urban growth into a single generalization of both the Eden and the p-models. Calibration strategy was demonstrated using historical aerial photographs of Saga city, Japan.